2016
DOI: 10.1177/0739456x16657874
|View full text |Cite
|
Sign up to set email alerts
|

Equity Planning or Equitable Opportunities? The Construction of Equity in the HUD Sustainable Communities Regional Planning Grants

Abstract: In this article, we examine recent efforts by the federal government to promote regional planning that incorporates social equity into sustainability and livability principles through the Sustainable Communities Regional Planning Grant (SCRPG). We use a plan quality analysis framework to examine grant proposals from the 2010 awardees. The analysis asks whether these regional plan proposals represent a new equity planning or if regional-scale equity policy remains obscured in quality of life arguments. We concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Seattle's plan addressed displacement and increased staff to develop affordable housing. It also included detailed funding arrangements (such as tax increment financing alternatives) to implement affordable housing strategies (Zapata and Bates 2017). However, a review (Zapata and Bates 2017) of the SCRPGP found that many of the grantees did not comprehensively address affordable housing and the proposals contained few concrete plans to target low-income earners (such as inclusionary zoning).…”
Section: The Sustainable Communities Regional Planning Grant Programmentioning
confidence: 99%
“…Seattle's plan addressed displacement and increased staff to develop affordable housing. It also included detailed funding arrangements (such as tax increment financing alternatives) to implement affordable housing strategies (Zapata and Bates 2017). However, a review (Zapata and Bates 2017) of the SCRPGP found that many of the grantees did not comprehensively address affordable housing and the proposals contained few concrete plans to target low-income earners (such as inclusionary zoning).…”
Section: The Sustainable Communities Regional Planning Grant Programmentioning
confidence: 99%
“…The way CBO leaders in this study defined sustainable communities closely aligned with the focus of international NGOs working solely on sustainable community pursuits. With over three decades of experience and over 100 projects in 30…”
Section: Discussionmentioning
confidence: 99%
“…Partnerships and collaborations have a significant role in creating a more deliberative and inclusive framework for sustainable community pursuits [20,[27][28][29]]. An examination of U.S. Federal Government's Sustainable Communities Regional Planning Grant, an effort to promote regional planning that incorporated social equity into sustainability, while regional equity planning remained lacking, determined that some organizations were making headway, particularly those that considered economic and racial segregation, clearly defined policy work toward addressing specific underserved communities, and discussed strategies to engage multiple jurisdictions and stakeholders [30]. As Agyeman and Evans wrote, "if enough examples of sustainability and environmental justice initiatives can be created and networked, then perhaps this can galvanize a movement to reinvent the definition of progress [31]."…”
Section: Discussionmentioning
confidence: 99%
“…Planners who study hazards are concerned about social vulnerability because disadvantaged people are more likely to live in lower quality housing in areas more affected by storms and less likely to hear and believe warnings, have the means to evacuate, and eventually recover (Van Zandt et al, 2012;Zahran et al, 2008). Disadvantaged people are also more likely to be affected by exposure to natural and human-caused environmental hazards, many of which are becoming more extreme as the climate becomes warmer (Heckert & Rosan, 2016;Osland, 2011).…”
Section: What Does Equitable Planning Look Like?mentioning
confidence: 99%